Introducing the Delsarte system of vocal expression in nineteenth-century London - Hoover, B (2021)
My presentation investigates François Delsarte’s system of expression, its entry into the London music schools through the teachings of Manuel Garcia Jr. and his son Gustave, and its influence on the musical writings of George Bernard Shaw. While it is known to theatre historians that Delsarte’s system of gesture was widely used in dramatic training at the end of the nineteenth and into the twentieth century, the original system was, in fact, a musico-aesthetic system of training which could be applied to any and all art forms, not only performance. The system was based on the concept of the ‘Ninth Chord,” that is three interlocking perfect triads as a manifestation of the Holy Trinity in sound, which sympathetically correspond to, and thus have the power to order, the tripartite human soul. This presentation marks the initial stage of my research into Delsarte’s contribution to the science of vocal pedagogy, and his influence on vocal pedagogy in nineteenth-century London, so please note that my findings are still tentative at this point.